2015
DOI: 10.15547/bjvm.806
|View full text |Cite
|
Sign up to set email alerts
|

A review on urolithiasis in dogs and cats

Abstract: Urolithiasis is a nutritional disease that affects domestic carnivores. Past and recent literature on urolithiasis was reviewed for information on anatomical occurrence, physiology of urine formation, prevalence, mineral composition, clinical signs, laboratory findings, dissolution therapy, surgery and prevention of urolithiasis. The acquired knowledge of complexed and multifaceted urolithiasis is a tremendous achievement towards the treatment and control of the disease. However, eradication of the disease is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 50 publications
0
26
0
18
Order By: Relevance
“…Urolithiasis due to calcium oxalate calculi is relatively uncommon, with calcium carbonate calculi tending to develop more commonly in animals grazing on oxalate containing plants [8]. Recently, [9] reported that the most common component in canine uroliths is struvite (magnesium ammonium phosphate). High incidence of inflammations of the urinary bladder in equine, 19.55% reported in Perillo et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Urolithiasis due to calcium oxalate calculi is relatively uncommon, with calcium carbonate calculi tending to develop more commonly in animals grazing on oxalate containing plants [8]. Recently, [9] reported that the most common component in canine uroliths is struvite (magnesium ammonium phosphate). High incidence of inflammations of the urinary bladder in equine, 19.55% reported in Perillo et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Palpation during physical examination showed that there was a huge mass in the coealomic cavity which indicates a urolithiasis in the bladder (Blahak, 1994). Size range of urolith varies from sandlike material to large individual stones that may grow filling entire urinary bladder (Tion et al, 2015). Radiography was performed to confirm the size and amount of the urolith stone.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic saline (20%) could decrease hematocrit, total protein, and albumin [58] invariably decreasing erythrocytes and perhaps increasing hemoglobin. Toxic agents such as plants, drugs, venoms, antivenoms, chemicals, uroliths, and some food additives could damage erythrocytes and consequently cause anemia [59,61]. Halofantrine, sulfadimidine, chloramphenicol, and other many drugs and chemicals are toxic to erythrocytes [10,15,62].…”
Section: Effects Of Toxic Agents On Erythrocytesmentioning
confidence: 99%